The Cultivating Siri's Cultural Values in Child Character Building - Syahrir, Musdalifah; Sugiati, Andi; Wiranti, Wiranti; Fitriasari, Susan; Suriaman, Suriaman (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
The purpose of this study is to describe and analyze the cultivation of siri' cultural values in the formation of children's character in Lompo Riaja Village, Tanete Riaja District, Barru Regency, to describe and analyze the factors that support the cultivation of siri' cultural values in the formation of children's character in Lompo Riaja Village, Tanete Riaja District, Barru Regency. This type of research is qualitative research, whereas qualitative research is descriptive research. This research was in Lompo Riaja Village, Tanete Riaja District, Barru Regency. The choice of this research place was based on consideration because in Lompo Riaja Village, the culture of siri' has begun to fade. The research subjects were five parents and five children (sources or informants) who could provide information about problems related to the research to be carried out. The research instruments used were observation sheets, interview guidelines, and documentation. Data collection techniques were observation, interview, and documentation. The analysis techniques used in this research were data reduction, data presentation, conclusions, and verification. Based on the results of research conducted in Lompo Riaja Village, Tanete Riaja Subdistrict, Barru Regency, the results are based on the cultural value of honesty because honesty is one of the primary keys that is considered essential for parents, which will have a major impact on children's future lives. Through honesty, children can interact with their environment well, and good faith will be a guide in influencing the sea of life and leading children's lives in a better direction. The character of children based on siri' cultural values in Lompo Riaja Village, Tanete Riaja Sub-district, Barru Regency is inseparable from the various obstacles faced by parents, where environmental factors and technological developments are one of the main problems that can make children's character change following their surroundings.